Aristotle's practical side : on his psychology, ethics, politics and rhetoric - Fortenbaugh, William W. (Philosophia Antiqua, 2006)
This volume focuses on Aristotle's practical philosophy. His analysis of emotional response takes pride of place. It is followed by discussion of his moral psychology: the division of the human soul into emotional and deliberative parts. Moral virtue is studied in relation to emotion, and animals are shown to lack both emotion and virtue. Different kinds of friendship are analyzed, and the effects of vehemence, id est, temperament are given special attention. Aristotle's justification for assigning natural slaves and women subordinate roles receives detailed consideration. The same is true of his analysis of correct and incorrect constitutions. Finally, persuasion is taken up from several angles including Aristotle's emphasis on the presentation of character and his curious dismissal of delivery in speech.